Comparing self-esteem and self-compassion: an analysis within the big five personality traits framework - Yang, Fan; Hagiwara, Chiaki; Kotani, Tomomi; Hirao, Joji; Oshio, Atsushi (Frontiers in Psychology, 2023)
Self-esteem and self-compassion are two ways to relate to oneself. However, little is known about the similarities and differences between these two constructs. The current study used cross-sectional data from a Japanese sample to explore their relationship from a Big Five perspective. Results showed that differences between self-esteem and self-compassion appeared mainly in openness, agreeableness, and neuroticism. Specifically, self-esteem was uniquely associated with openness, and self-compassion was uniquely associated with agreeableness. Moreover, the negative correlation between self-compassion and neuroticism was larger than that between self-esteem and neuroticism. Implications and future directions are discussed.